The water mite genus Gretacarus K.O. Viets, 1978 from Australia (Acari: Hydrachnidia, Mideopsidae: Gretacarinae), with the description of three new species - Smit, Harry (Zootaxa, 2016)
Three new species of the genus Gretacarus K.O. Viets, 1984 are described from Australia, G. gereckei n. sp., G. occidentalis n. sp. and G. yorkensis n. sp.. Moreover, many new records are given for other members of the genus.